Functional genomic screening identifies dual leucine zipper kinase as a key mediator of retinal ganglion cell death - Welsbie, Derek S.; Yang, Zhiyong; Ge, Yan; Mitchell, Katherine L.; Zhou, Xinrong; Martin, Scott E.; Berlinicke, Cynthia A.; Hackler, Laszlo; Fuller, John; Fu, Jie; Cao, Li-hui; Han, Bing; et al. (Proceedings of the National Academy of Sciences - PNAS, 2013)
Glaucoma, a major cause of blindness worldwide, is a neurodegenerative optic neuropathy in which vision loss is caused by loss of retinal ganglion cells (RGCs). To better define the pathways mediating RGC death and identify targets for the development of neuroprotective drugs, we developed a high-throughput RNA interference screen with primary RGCs and used it to screen the full mouse kinome. The screen identified dual leucine zipper kinase (DLK) as a key neuroprotective target in RGCs. In cultured RGCs, DLK signaling is both necessary and sufficient for cell death. DLK undergoes robust posttranscriptional up-regulation in response to axonal injury in vitro and in vivo. Using a conditional knockout approach, we confirmed that DLK is required for RGC JNK activation and cell death in a rodent model of optic neuropathy. In addition, tozasertib, a small molecule protein kinase inhibitor with activity against DLK, protects RGCs from cell death in rodent glaucoma and traumatic optic neuropathy models. Together, our results establish a previously undescribed drug/drug target combination in glaucoma, identify an early marker of RGC injury, and provide a starting point for the development of more specific neuroprotective DLK inhibitors for the treatment of glaucoma, nonglaucomatous forms of optic neuropathy, and perhaps other CNS neurodegenerations.